Circulating angiotensin-converting enzyme 2 concentration is associated with acute kidney injury and mortality in sepsis - Ching-En Chen; Ruey-Hsing Chou; Jiun-Yu Guo; Ya-Wen Lu; Chun-Chin Chang; Cheng-Hsueh Wu; Po-Hsun Huang (PLoS ONE, 2025)
Background Beyond the well-established classical renin-angiotensin system (RAS), emerging evidence highlights the critical role of the non-classical RAS, specifically the Angiotensin (1–7)/ACE2/Mas axis. As the key enzyme converting Angiotensin II into Angiotensin (1–7), angiotensin-converting enzyme 2 (ACE2) exerts cardioprotective and anti-inflammatory effects, showing potential therapeutic value in critical care. This study investigates the association between circulating ACE2 levels and clinical outcomes in sepsis, offering insights into its role and potential for predicting sepsis outcomes. Materials and methods In this single-center study, we investigated associations between the circulating ACE2 concentration and outcomes in septic patients admitted to a medical intensive care unit (ICU) between 01/05/2018 and 31/01/2021. Sepsis was defined as infection accompanied by a ≥2-point Sequential Organ Failure Assessment (SOFA) score increase. Patients were categorized into low (<2.5 ng/mL) and high (≥2.5 ng/mL) ACE2 groups based on serum concentrations within 24 hours of ICU admission. Outcomes comprised acute kidney injury (AKI), ICU mortality, and 90-day mortality. Results In total, 414 patients (mean age 68.5 years, 64.7% male) were included in the study. Elevated ACE2 levels correlated positively with SOFA score and total bilirubin and lactate concentrations, and negatively with the hemoglobin concentration. Relative to the low ACE2 group, the high ACE2 group was at increased risk of sepsis-associated AKI development within 48 hours after ICU admission (81.6% vs. 69.6%, p = 0.006), AKI requiring renal replacement therapy (21.3% vs. 11.1%, p = 0.007), ICU mortality (31.9% vs. 17.5%, p = 0.001), and 90-day mortality (51.7% vs. 39.6%, p = 0.018). Kaplan-Meier survival curves demonstrated significantly reduced survival in individuals with high ACE2 concentrations (p = 0.009). Univariate analysis revealed significant associations of high ACE2 concentrations with ICU mortality and AKI development within 48 hours after ICU admission. In a multivariate analysis adjusted for relevant variables, ACE2 elevation remained an independent predictor of ICU mortality (adjusted odds ratio 2.15, 95% confidence interval 1.04–4.41, p = 0.038). Conclusion Elevated circulating ACE2 concentrations comprised an independent predictor of ICU mortality, highlighting intricate RAS dynamics in critical illnesses. Low ACE2 concentrations were associated with greater survival, suggesting their potential as an early prognostic indicator.